Science and theology - Tałasiewicz, Mieszko (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
According to a popular view science and theology are incompatible: non-overlapping magisteria, in terms of the object of their pursuit. In this paper I will argue that the relation which exists between science and theology is neither that of separation nor local explication but the complete inclusion of one within the other. From the point of view of religion, namely, science in fact is contained in a broadly understood theology. This claim counters the common view that science and theology are concerned with different ontological orders: the natural and the supernatural. From the Christian point of view there is no question of there being any different orders. There is one order: God made Heaven and Earth, including all things on Earth and all the laws which govern them; thus natural sciences, as concerning some of the God’s creatures, are subsumed under theology. It doesn’t yield anything like the subservience of natural sciences to theological dictates, though. The scientific methods of studying the world are the product of our efforts, and the proposition that the world was created by God, or that it wasn’t, does not change anything. Sciences have no bearing on what was revealed. Yet if we are to follow the teachings of Revelation as regards how to act and what not to do, we would need knowledge – in matters of physics, psychology and biology – about the mechanisms which we, as biological organisms, rely on for our natural behaviour. To this extent theology should be interested in studying the actual biological, cultural and social determinants of man’s existence so that he could make the most of the favoring circumstances while guarding against circumstances which conspire against him. Theology asks these questions of science, and if it wants to be rational, it should respect the answers, whatever they may be. The relation holds in one direction: science says how things are; theology takes it on board and tries to work out how to use it to aid in the understanding of Revelation. Telling science what theology would like to hear is devoid of purpose. There are no good or bad answers. As the illustration I discuss the so called ‘God gene’ hypothesis (Dean Hammer), ‘Libet’s effect’ (Benjamin Libet) and innate moral sense (Marc Hauser) showing how theology can gain inspiration from proper acknowledgement of such phenomena.